2007
DOI: 10.1136/thx.2007.083717
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pulmonary alveolar infiltrate and prostate tumour in a 54-year-old man

Abstract: 13 Hasford J, Fagerstrom KO, Haustein KO. A naturalistic cohort study on effectiveness, safety and usage pattern of an over-the-counter nicotine patch. Cohort study on smoking cessation. Eur J Clin Pharmacol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Embryonal prostatic rhabdomyosarcoma that occurs predominantly in male infants and children (median age of 5 years) is a rare and highly malignant tumour. Only sporadic cases have been reported in non-pediatric age group [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonal prostatic rhabdomyosarcoma that occurs predominantly in male infants and children (median age of 5 years) is a rare and highly malignant tumour. Only sporadic cases have been reported in non-pediatric age group [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features of EPRM published in literature include rapidly progressive obstructive urinary symptoms, smooth and firm enlargement of prostate on digital rectal examination, occasional suprapubic mass, regional lymph node spread, respiratory symptoms due to metastasis to lungs, osteoclastic bone metastases, and normal prostatic acid phosphates and prostate specific antigen levels [ 1 , 2 , 3 ]. The case presented here is atypical in terms of its inconspicuous presentation mimicking a systemic inflammatory response and in the authors’ best knowledge has not been reported before.…”
Section: Discussionmentioning
confidence: 99%